Radiologic Severity Index (RSI) Score in COVID-19 Patients After Administration of Remdesivir: A Study on High CRP and D-dimer Levels in a Group of Patients - Adhi Rommy Setyawan; Bambang Satoto; Sofyan Budi Raharjo; Christina Hari Nawangsih; Hermina Sukmaningtyas; Nurdopo Baskoro (RSUP Dr. Kariadi, 2025)
BACKGROUND: The COVID-19 pandemic has high mortality and morbidity. The lungs are the main target organ with a variety of symptoms ranging from asymptomatic to respiratory failure. Chest X-ray plays an important role in diagnosis, management, and prognosis. One of the chest X-ray assessment systems used is the Radiology Severity Index (RSI). Serum CRP and D-dimer levels can also be used to determine the severity of COVID-19. AIM: To examine changes in RSI scores after remdesivir therapy in COVID-19 patients with high CRP and D-dimer values. METHOD: A prospective cohort study of 64 COVID-19 patients at Dr. Kariadi Hospital Semarang from July 2020 to July 2021. Each consisted of 32 patients with high CRP (>5 mg/L) and D-dimer (>500 ng/mL) levels. Patients were given Remdesivir 200 mg therapy on day 1, followed by 100 mg/day until day 9. Chest X-rays were performed before and on day 7 after initial therapy. Patients with CHF, malignancy, autoimmune, pulmonary TB, interstitial lung disease and receiving azythromycin therapy were excluded from the study. Correlation analysis between variables was performed using the Spearman rho test and comparison test between groups. Significant results if p <0.05. RESULT: There was a significant decrease in the RSI score of COVID-19 patients with high CRP and D-dimer levels after therapy, from 21.97±16.88 and 21.22±19.92 to 15.69±14.12 and 15.78±15.69, respectively (p<0.001). There was a weak significant relationship between high CRP levels and pre-therapy RSI scores (r=0.473, p=0.006) and high D-dimer levels and post-therapy RSI scores (r=0.362, p=0.041). CONCLUSION: Remdesivir provides a significant correlation in the form of a decrease in RSI scores in COVID-19 patients with high CRP or D-dimer levels.